Preliminary Results of Cord Blood Mononuclear Cell Therapy for Multiple System Atrophy: A Report of Three Cases - Wu, Shu-Hui (Med Princ Pract, 2014)
OBJECTIVES: This study was designed to evaluate the effects of cord blood mononuclear cell transplantation in multiple system atrophy (MSA). CLINICAL PRESENTATION AND INTERVENTION: Cord blood mononuclear cells (1-2 × 10(8) cells/6 ml) were injected into the subarachnoid space using lumbar puncture in patients 1 and 2 and cisterna magna puncture in patient 3 in the 3 patients with MSA. The cord blood mononuclear cell transplantation was repeated 30 days after the first treatment in patients 1 and 2; it was repeated twice in patient 3. The clinical outcomes of treatment were used to assess the Unified Multiple System Atrophy Rating Scale (UMSARS) before, 90 and 180 days after the cell transplantation. There were no clinically noticeable side effects from the cord blood mononuclear cells. The UMSARS scores improved after 90 days of the cord blood mononuclear cell therapy in all 3 patients, the most significant improvement being that in urinary incontinence and ability to walk. CONCLUSIONS: Cord blood mononuclear cell transplantation was safe and potentially effective in the treatment of MSA in the 3 patients.